AN ANALYSIS OF OUTER CODE SWITCHING AND CODE MIXING IN INDONESIA LAWYERS CLUB - Dewi, Citra; Ekalaya, Yayan (LITERARY CRITICISM, 2015)
Outer code switching and code mixing commonly exist in conversation especially in bilingual or multilingial community. The higer speakersâ ability in bilingual or multilingual, the more code switching and code mixing occure. Indonesia Lawyers Club(ILC) is one example academic people and profesionals within community frequently use code switching and code mixing as speakers in that dialog program on television. The relation between speakers in ILC and outer code switching and code mixing attracted the writerâs attention to do this study as in the objective study stated: (1) To find out what are the types of Outer Code Switching and Code Mixing in ILC.(2)To explain in what context the people in Indonesia Lawyers Club do their Code Switching and Code Mixing. The design of this study is content analysis. It describes the analysis base on what the writer found inthe study object ILC.The result of this study are: (1) The types of outer code switching and code mixing used in ILC are: seventeen Inter-sentential switching, five emblematic switching, three hundreed and thiry nine Intra-sentential switching, fifty three Intra lexical, and seven Involving change pronounciation. So, there is no doubt that Intra-sentential becomes the most dominant and Emblematic Switching is not dominant. (2) The contextual reason found in Indonesia Lawyers Club are: Expressing Identity with three hundreed occurences, continue with eighty four Lexical Need, nineteen Repetition, twelve Quoting, five Interjection, and two Clarifying. So, the theory from Hoffman about code switching and code mixing and also his theory about Reason supported by Saville-Trioke are stick with the result of the study that people in ILC dominantly use code mixing that the mixing occurrences are within sentence and the reason why people in ILC do outer code switching and code mixing is to express group identity.Â Keywords: Outer code switching and code mixing, Indonesia Lawyers Club.